The export marketing imperative - Czinkota, Michael R. (Thomson, 2004)
Increasing competition and mounting pressure to boost revenues leave limited growth options for some companies, prompting many to turn a hopeful eye toward international markets. A must-read for anyone interested in breaking into global markets, The Export Marketing Imperative walks readers through the entire exporting process — from beginning to end — offering a wealth of information with its comprehensive coverage of all facets of exporting.